The Pathosome: A Dynamic Three-Dimensional View of Disease-Environment Interaction - Lenart, Peter; Scheringer, Martin; Bienertova-Vasku, Julie (BioEssays, 2019)
Most contemporary models of disease development consider the interaction between genotype and environment as static. The authors argue that because time is a key factor in genotype-environment interaction, this approach oversimplifies the pathology analysis and may lead to wrong conclusions. In reviewing the field, the authors suggest that the history of genotype-environment interactions plays an important role in the development of diseases and that this history may be analyzed using the phenotype as a proxy. Furthermore, a theoretical and experimental framework is proposed based on the assumption that phenotypes do not change from one to another randomly but are interconnected and follow certain phenotype trajectories. It then follows that analysis of such phenotype trajectories might be useful to predict the future phenotypes including the onset of disease. In addition, an analysis of phenotype trajectories can be subsequently used to choose better control subjects in comparative studies reducing noise and bias in studies investigating disease mechanisms.
Keywords: nemoc; Genetic Predisposition to Disease; Models, Genetic; health; čas; preconditioning; modely genetické; Aging; pathosome; zkreslení výsledků (epidemiologie); genotyp; Genotype; disease; Bias; genetická variace; Gene-Environment Interaction; environment; Genetic Variation; stárnutí; Time; Disease; Humans; epidemiologické metody; Epidemiologic Methods; Pathology; phenotype; interakce genů a prostředí; genetická predispozice k nemoci; patologie; lidé